2015
DOI: 10.1002/bse.1879
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Leaders Promote Sustainability? Analyzing the Effect of Corporate Governance Composition on Environmental Performance

Abstract: In this study, we investigate the impact women leaders have on the corporate environmental strategies of organizations. Using a dataset of all Fortune 500 CEOs and boards of directors for a ten‐year period, we examine several aspects of gender in leadership on environmental strategy. Specifically, we test the impact of women CEOs, the proportion of women on the BOD, the number of interlinks women board members hold, and the interactive and cumulative effects of women CEOs and gender diverse boards. Findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
408
4
5

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 426 publications
(511 citation statements)
references
References 94 publications
38
408
4
5
Order By: Relevance
“…These results are also consistent with the argument that large boards are not as cohesive in initiating strategic action compared to smaller boards and that, as a result, perform less strategic planning and may encounter more problems in setting and implementing an acceptable agenda on the environment. Our finding of a statistically significant negative association between the presence of a woman on the board and the likelihood of a firm being convicted of an environmental offence is also consistent with growing literature showing the effectiveness of women on the board of directors (e.g., Glass et al, 2015;Post el al., 2015). These findings are also consistent with the suggestion by Hillman et al (2002) that women on boards are more likely than men to be support specialists and individuals with influence in the community and that having more female directors may sensitize boards to CSR initiatives.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are also consistent with the argument that large boards are not as cohesive in initiating strategic action compared to smaller boards and that, as a result, perform less strategic planning and may encounter more problems in setting and implementing an acceptable agenda on the environment. Our finding of a statistically significant negative association between the presence of a woman on the board and the likelihood of a firm being convicted of an environmental offence is also consistent with growing literature showing the effectiveness of women on the board of directors (e.g., Glass et al, 2015;Post el al., 2015). These findings are also consistent with the suggestion by Hillman et al (2002) that women on boards are more likely than men to be support specialists and individuals with influence in the community and that having more female directors may sensitize boards to CSR initiatives.…”
Section: Discussionsupporting
confidence: 91%
“…Glass, Cook and Ingersoll (2015) investigated the impact women leaders had on the corporate environmental strategies of organisations. The findings revealed that the effects of gender diversity on environmental practice are nuanced and context dependent.…”
Section: Prior Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive business case for board gender diversity (also referred to as the utility argument) was observed by several authors (Adams & Ferreira 2009;Seierstad 2016;Simpson, Carter & D'Souza 2010). In addition to financial benefits, gender diverse boards are associated with proactive social and environmental policies, practices and reporting (Bernardi & Threadgill 2010;Glass, Cook & Ingersoll 2015). Bear, Rahman and Post (2010) reported a positive association between board gender diversity and a company's reputation as a good corporate citizen.…”
Section: Benefits Concerns and Possible Reasons For The Low Level Ofmentioning
confidence: 99%